A rare case of multifocal atypical teratoid rhabdoid tumor - Nguyen Minh Duc, MD (Radiology Case Reports, 2023)
Atypical rhabdoid teratoid tumor of the primary central nervous system is an uncommon and highly aggressive tumor that often affects infants and young children. Approximately two-thirds of tumors start in the posterior fossa. The best treatment for atypical rhabdoid teratoid tumor is yet unknown. Chemotherapy, radiation, and surgery are available as treatment options. Their respective roles are yet not each well defined. The prognosis for atypical rhabdoid teratoid tumor is absolutely poor. In this article, we intended to introduce a very rare case of multifocal atypical rhabdoid teratoid tumor in a 7-year-old boy.